THE EFFECT OF BONUS MECHANISM TAX AND TUNNELING INCENTIVE ON INDICATIONS OF TRANSFER PRICING IN MANUFACTURING COMPANIES REGISTERED IN INDONESIA STOCK EXCHANGE FOR 2017-2019 - Teguh Purnomo; Pristiwantiyasih Pristiwantiyasih; Mochamad Ardi Setyawan (Media Mahardhika, 2021)
This examination intends to decide the connection between Tax Influence, Bonus Mechanism, and Tunneling Incentive on signs of move estimating. The example utilized is the purchaser merchandise sub-area producing organizations recorded on the Indonesia Stock Exchange (IDX) for the period 2017 - 2019. The technique used to take tests is the purposive inspecting strategy and the information investigation strategy utilized is numerous straight examination. The outcomes show that Simultaneously, charges, extra systems and burrowing motivations affect move valuing. While somewhat, tuneling motivators influence move estimating. Duties and extra components don't influence move evaluating. The coefficient of assurance test results show that the coefficient of assurance is 0.284. This shows that the free factors utilized in the relapse model, specifically Tax, Bonus Mechanism, and Tunneling Incentive can clarify their impact on the reliant variable exchange estimating by 28.4%. While the excess 71.6% is clarified by different elements.